A disconnect in media accountability: Spanish journalists' and citizens' perceptions of established and innovative instruments at the organizational level. (1st March 2022) - Ramon, Xavier; Mauri-Ríos, Marcel; Díaz-Campo, Jesús; Suárez-Villegas, Juan Carlos
In the current media landscape, accountability can be promoted through a wide range of established and innovative instruments. Focusing on the Spanish context, this article examines journalists' perceptions of in-house accountability instrument effectiveness and analyses citizens' knowledge and understanding of these mechanisms. A mixed- methods approach was employed: an online survey was administered to Spanish journalists (N = 228), and six citizen focus groups (38 participants in total) were established in several regions of Spain (Andalusia, Basque Country, Catalonia, Galicia, Madrid and Valencia). Findings showed that journalists' evaluation of media accountability instruments is remarkably limited, scoring 5.82 out of 10 points in the highest case. From the citizens' perspective, the overwhelming lack of visibility and relative distrust towards these instruments are revealed. This double disconnect from accountability brings to light the need to rethink and reinvigorate the existing instruments so they can effectively contribute to the goal of rebuilding trust in journalism.